Manfaat Program Layanan BPJS Ketenagakerjaan Bagi Kesejahteraan Masyarakat: (Magang Mitra USU di BPJS Ketenagakerjaan Medan Kota) - Indah Lestari Sihombing; Fajar Utama Ritonga (Yayasan Literasi Sains Indonesia, 2024)
BPJS Employment, formerly known as Jamsostek, has undergone a lengthy evolution in providing protection to workers and their families in Indonesia. Since its inception regulated by a series of laws and regulations, until becoming part of the National Social Security System under Law No. 40 of 2004, BPJS Employment has provided various assurance programs covering work accidents, death, old age, pensions, and job loss. Through interviews with traders, farmers, and factory workers, it is evident that these programs provide significant benefits, such as a sense of security and financial protection, which positively impact work productivity. However, public awareness of the importance of employment social security still needs to be increased through broader socialization. Thus, BPJS Employment is not only a financial protection instrument for workers but also plays a role in improving the overall welfare of society.